Spatial Pattern Change of The Nagari Sianok Anam Suku - Rinaldi Mirsa; Muhammad; Rendi Setiawan (Jurnal Inovasi Teknologi, 2021)
Nagari Sianok Anam Suku is a historical village where 6 indigenous Minangkabau tribes’ settlements have lived since the 16th century. Due to the urbanization development era in Bukit Tinggi City, forcing the surrounding area to change the Nagari Sianok Anam Spatial Pattern; Mass Layout, Road Network, Land Use, Building Forms, and Open Space. The purpose of this study is to analyze changes in the spatial pattern of the Nagari Sianok Anam Suku which is adjacent to Bukit Tinggi City. The method used is a descriptive quantitative method, the researcher aims to describe how spatial pattern change occurred. It can be seen from spatial changes analysis in the Sianok Anam Suku area from 16th to 20th centuries how area change was carried out by the people living in the area.